Bunin in the Interwar Poland. A Failed Tour - Iwona Anna Ndiaye (Studia Litterarum)
The following paper explores the reception of Ivan Bunin’s literary legacy in the interwar Poland. The question of how The Nobel Prize in Literature influenced the writer’s popularity in Poland. The main aim of this article is to analyze and characterize those circumstances, which became the reason for Bunin’s failure to visit Poland during his literary tour to the Baltic countries in 1938. Selected materials were taken from traditional card and online catalogues in the National Library of Poland and the University of Warsaw Library. They embrace the period from 1920 to 1940. The analysis, on the one hand, shows the problem of political relationships between the revived Polish state and young Soviet Russia and its role in the development of literary contacts in the interwar period. On the other hand, it allows us to draw conclusions about the political and literary dimensions of I. Bunin’s failed tour to Poland.